2003
DOI: 10.1097/01.psy.0000097345.73308.c6
|View full text |Cite
|
Sign up to set email alerts
|

Resting End-Tidal CO2 and Negative Affectivity

Abstract: Overall, no association between dispositional NA and cross-situational FetCO2 was observed. Apparently inconsistent findings may be caused by lack of control for hormonal status and mental load during testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
1
14
1
Order By: Relevance
“…In line with previous findings showing only weak negative associations between P et CO 2 and symptom perception (23)(24), we found no significant coherence between P et CO 2 and the selfreported affective experience, or between P et CO 2 and the self-reported physiological symptoms. Therefore, and given the highly normal P et CO 2 values, it is unlikely that symptom perception was due to hyperventilation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In line with previous findings showing only weak negative associations between P et CO 2 and symptom perception (23)(24), we found no significant coherence between P et CO 2 and the selfreported affective experience, or between P et CO 2 and the self-reported physiological symptoms. Therefore, and given the highly normal P et CO 2 values, it is unlikely that symptom perception was due to hyperventilation.…”
Section: Discussionsupporting
confidence: 81%
“…Gender, voluntary control of respiration, and ACC were additionally included because of their potential influence on the dependent variables 2 . When modeling P et CO 2 , we also included hormonal contraception as a potential confounder (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 to .50 has been found systematically between NA ratings and subjective symptom scores. These subjective complaints are rarely associated with NA-related differences in objective health problems [12,18,19], nor with differences in autonomic or respiratory responses [20,21]. In the respiratory domain, it has been observed that high-NA asthmatics report more symptoms, are more inclined to use medication, and appear to have a higher chance to become hospitalized, regardless of their pulmonary status [22,23].…”
Section: Introductionmentioning
confidence: 95%
“…Another one is negative affectivity, i.e., the general tendency to experience negative emotions and self-image, introversion, and dwelling on failures and shortcomings. Individuals with a high level of negative affectivity tend to report more frequent and more severe dyspnea [120][121][122][123]. Also, patients with non-organic dyspnea seem to be more anxious and to report dyspnea more often than patients with dyspnea that accompanies pathologic changes [124].…”
Section: General Therapeutic Principles Of Dyspneamentioning
confidence: 99%